Effect of Ba-deficiency on the phase and structural stability of (BaSr)(CeZr)O-3-based proton conducting oxides - Jaiswal, Shivendra Kumar; Choi, Sung Min; Yoon, Kyung Joong; Son, Ji-Won; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Deficiency in proton conducting perovskite-type oxides can be strongly influence the fuel cell properties. The effect of barium deficiency on the phase structure, cerium oxidation states, electrical conductivity and phase stability under carbon dioxide atmosphere of proton conducting oxides with composition of (Ba0.6-pSr0.4)(Ce0.75Zr0.10Y0.15)O3-delta (p - barium deficiency; 0.025 <= p <= 0.20) was systematically investigated. Rietveld refinement of the X-ray diffraction patterns shows the cubic structure in the space group Pm-3m up to p = 0.10. The lattice parameter decreases with 'p' and lie in the range similar to 4.358 to similar to 4.333 angstrom. XPS data show the percentage of Ce4+ increases which in turn, reduces the oxygen non-stoichiometry (delta) - values with deficiency (p). Raman spectra show the presence of oxygen vacancies which decreases with 'p'. The conduction behavior depicts the protonic nature with activation energy lying in the range of 0.24-0.29 eV. The stability of deficient compositions (0.025 <= p <= 0.20) enhances in carbon dioxide (CO2) atmosphere in compare to p=0. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CHEMICAL-STABILITY; FUEL-CELLS; ELECTRICAL-CONDUCTIVITY; CATION NONSTOICHIOMETRY; TRANSPORT-PROPERTIES; COMPOSITE CATHODE; IONIC-CONDUCTION; SINTERED OXIDES; DOPED BACEO3; WATER-VAPOR